2018
DOI: 10.1149/2.0931816jes
|View full text |Cite
|
Sign up to set email alerts
|

PEM Fuel Cell Start-Up/Shut-Down Losses vs Relative Humidity: The Impact of Water in the Electrode Layer on Carbon Corrosion

Abstract: For automotive applications, one of the main challenges for proton exchange membrane fuel cells (PEMFCs) is to increase the lifetime of membrane electrode assemblies (MEAs), especially during transient operating conditions such as start-up/shut-down (SUSD) cycles. During SUSD, the carbon support in the cathode layer is known to be oxidized as a consequence of hydrogen/air anode gas fronts moving through the anode. In this work, we focus on the effect of relative humidity (RH) during SUSD events. Here we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 28 publications
0
44
1
Order By: Relevance
“…However, the abundant defect and edge sites of a GNR can also be a disadvantage in using support materials because they would inevitably be the initial point of carbon corrosion 20 . Carbon corrosion is one of the most problematic degradation mechanisms in carbon-based support materials because it leads to side effects such as Pt agglomeration and detachment under carbon corrosion conditions [21][22][23] . Therefore, GNR might not be suitable as a support material because it is imperatively vulnerable to carbon corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…However, the abundant defect and edge sites of a GNR can also be a disadvantage in using support materials because they would inevitably be the initial point of carbon corrosion 20 . Carbon corrosion is one of the most problematic degradation mechanisms in carbon-based support materials because it leads to side effects such as Pt agglomeration and detachment under carbon corrosion conditions [21][22][23] . Therefore, GNR might not be suitable as a support material because it is imperatively vulnerable to carbon corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…In our voltage cycling AST between 0.60 V and open circuit potential (OCV, approximately 0.94 V), the major electrocatalyst degradation mechanisms are expected to be Pt oxidation and reduction/dissolution and redisposition. Carbon-support corrosion is expected to be less severe at these conditions compared to those at high potentials above 1.2 V [24,25] . The loss of ECSA was observed to be 70% after voltage cycling, expected to be mostly due to Pt nano-particle size growth.…”
Section: Resultsmentioning
confidence: 98%
“…Figure 14 shows Polarization curves recorded before and after 60 SUSD cycles at 0.25, 0.4, 0.66, 0.80, 1.00 and wet RH, where "wet" denotes overhumidified gas at the inlet, with a minimum RH of 1.20. [131] For MEAs with electrodes based on Pt catalyst supported on high surface area carbon, the SUSD-induced degradation rate (expressed as mV cycle À 1 s À 1 ) was found to decrease by a factor of about 3 when the RH was reduced from 1.00 to 0.25 at 80°C during SUSD events. Very recent studies confirmed this finding under similar operating conditions.…”
Section: Effect Of Rh On Pem Fuel Cell Start-up/shut-down Lossesmentioning
confidence: 94%
“…[51] Mittermeier et al reported a study on the prediction and experimental determination of the SUSD damage induced by extended H 2 /air anode gas fronts as a function of RH. [131] To achieve this goal, the authors utilized on-line mass spectrometry in order to quantitatively determine the COR rate at 80°C vs potential and RH, and therefore determined the COR reaction order with respect to the RH. Figure 14 shows Polarization curves recorded before and after 60 SUSD cycles at 0.25, 0.4, 0.66, 0.80, 1.00 and wet RH, where "wet" denotes overhumidified gas at the inlet, with a minimum RH of 1.20.…”
Section: Effect Of Rh On Pem Fuel Cell Start-up/shut-down Lossesmentioning
confidence: 99%